Geometrical and Material Considerations for External Shading Optimisation of Residential Buildings in Southeastern Nigeria: A Systematic Review - Onwuzuligbo, Chijioke Chinyere; Uzoagba, Chidiebele Ejikeme Joseph; Umeora, Chukwunonso Obiefuna; Mmonwuba, Nwanneka Chibuzo (IPS Journal of Physical Sciences, 2025)
Background: The rising energy demand for cooling in residential buildings in Southeast Nigeria poses sustainability and energy security challenges. This study examines the optimisation of shading devices as a passive cooling strategy to enhance indoor thermal comfort by reducing solar heat gain in buildings. Objectives: To explore the geometric and material properties of external shading devices and how they can be applied for enhanced results, identify the challenges to devices in Southeast Nigeria, and recommend context-specific architectural and environmental recommendations for the region. Method: This scoping review employed thematic analysis to identify and summarise findings on considerations for optimizing external shading devices. Results: The findings revealed that properly designed shading systems, which consider shape, orientation, dimensions, and material properties, can significantly improve building energy efficiency. However, barriers such as the high cost of advanced shading materials, weak regulatory enforcement, and limited technical expertise hinder widespread implementation. Conclusion: External shading performance is impacted by topography and climatic changes throughout Southeast Nigeria, requiring context-specific strategies for maximum shading efficacy. This study recommends integrating vernacular shading techniques, optimising orientation and overhang design, and exploring sustainable material innovations to enhance shading efficiency. Further research is needed to develop cost-effective, durable shading solutions suited to the region’s climate and socioeconomic realities.